Assessing English Learning in Iceland. A Study of Assessment Methods Used in Icelandic Primary and Secondary Schools - Birna Margrét Arnþórsdóttir 1961- (2009)
This study examines assessment methods in English in Icelandic primary and secondary schools along with how assessment results are presented to students and parents. The study views which methods are used for summative assessment and whether there is variety in methods used for the various language skills. The study also examines whether formative assessment is practiced and in what form, and whether there is a difference in assessment methods between age levels and/or in relation to teachers’ education level and English teaching experience. The subjects of the study were English teachers of 11 secondary schools and 9 primary schools from all around the country. Data was collected through questionnaires via e-mail, and answers came from 24 secondary level teachers and 20 primary level teachers. Data was analysed statistically by the use of tables as well as verbal descriptions. The results show that written tests are the leading assessment method at both levels, usually counting for the majority of the final grade. However, some variety exists as all the participating teachers use other assessment methods as well. Listening and speaking skills are omitted in the assessment practices by some teachers, and formative assessment is currently not a high priority in the teachers’ choice of assessment practices. Assessment results are presented with a grade in all cases, however, the majority of primary level teachers, and 41% of secondary level teachers, also give oral and/or written comments. There is no obvious correlation between teachers’ education and experience, on the one hand, and choice of assessment methods on the other, however, an interesting difference appeared in how teachers’ education and experience vary between age levels.